Où commence la «Voie de la Vérité» et où finit la «Voie de la Doxa» chez Parménide? - Cordero , Nestor-Luis (Peitho. Examina Antiqua, 2024)
According to the “orthodox” version of Parmenides’ Poem, version generally accepted as vox dei, the “Way of Truth” begins in fragment 2 of the Poem (because fragment 1 is only a kind of introduction) and ends at verse 50 of fragment 8. The “Way of the Doxa”, on the other hand, begins at verse 51 of fragment 8 and ends at fragment 19. We believe it will not an be exaggeration to say that this text could be signed by most specialists interested in the Parmenidean philosophy, even the most eminent ones. Now, apart from a few words, this passage implicitly supposes a whole series of hypotheses, generally accepted without prior justification, hypotheses which, once analyzed, necessarily lead one to support the non-existence in Parmenides of either a “Way of Truth” or a “Way of Doxa”.